FORMATION OF ENVIRONMENTAL CONSCIOUSNESS FUTURE TEACHER AS A LEADING TASK OF ENVIRONMENTAL EDUCATION AND EDUCATION: MODERN APPROACHES TO THE DEFINITION OF THE CONCEPT ECOLOGICAL CULTURE (Pedagogy of Higher and Secondary Education, 2022)
This article is devoted to the modern problems of ecological consciousness forming of teachers and the lijferent apporoaches for definition of the essence, of the notion ecological consciousness are analysed.